On classification problem of Loday algebras - Sattarovich, Rakhimov Isamiddin (American Mathematical Society, 2016)
This is a survey paper on classification problems of some classes of algebras introduced by Loday around 1990s. In the paper the author intends to review the latest results on classification problem of Loday algebras, achievements have been made up to date, approaches and methods implemented.